2017
DOI: 10.1186/s40317-017-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in adverse effects of tracking devices on waterfowl requires better measuring and reporting

Abstract: Since the first studies in the mid-twentieth century, lightweight electronic tracking devices have been increasingly used to study waterfowl movements. With half a century of experience and growing sample sizes, it has become clear that the attachment of a tracking device can affect a bird's behaviour and fitness. This becomes problematic when it introduces uncertainty about whether the recorded data represent natural behaviour. Waterfowl may be particularly prone to tag effects, since many species are migrato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 68 publications
3
32
2
Order By: Relevance
“…Our results are concurrent with recent reviews on the negative effects of tracking devices on birds [2,26,40]. We show that harness-attached transmitters can negatively affect survival but also pair-bonding, and thus the potential of birds to initiate breeding.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our results are concurrent with recent reviews on the negative effects of tracking devices on birds [2,26,40]. We show that harness-attached transmitters can negatively affect survival but also pair-bonding, and thus the potential of birds to initiate breeding.…”
Section: Discussionsupporting
confidence: 76%
“…This may be caused by a change in behavior (e.g., increased time spent preening, [13]) or reduced flight maneuverability by the cross-sectional profile of the backpack tag causing additional drag [4], and perhaps not so much hunters targeting for marked geese [6]. Although our study found negative effects on return rates, our survival rates of tagged individuals were definitively higher than in some other studies [39], Harness attachments may have negative effects on survival, but are also likely to have non-lethal effects on migratory birds [26]. By using a control group from which we have individual data on migration timing gained from geolocators, we can show convincingly that harness attachments cause only a slight delay in timing of migration departure for barnacle geese.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Finally, most existing guidelines for tag impact do not advise on appropriate tag size, placement positions or configurations (Rosen et al, ) and many are relatively naïve to the impacts of drag that are most relevant to marine and aerial applications (see Appendix for an overview). We anticipate that the reporting of drag values in future publications may help improve future guidelines and address recent requests in the literature for improved reporting of impacts (Bodey et al, ; Lameris & Kleyheeg, ) and better assessment of tag‐induced effects (such as drag) prior to deployment in the field (Lear et al, ). While we do not expect our findings to be taken up as formal guidelines, nor the use of CFD to be made compulsory, we hope that this work, and specifically our step‐by‐step guide (Appendix ), will aid the biologging community in achieving this.…”
Section: Discussionmentioning
confidence: 99%
“…White et al (2013) compared the effects of external attachment with surgical implantation in a meta-analysis of 39 studies; consistent negative effects on body condition, reproduction, metabolism and survival were found with external attachment, whereas implanted devices had no consistent effects, although their use was associated with mortality resulting from the anaesthesia and surgery required for implantation. Lameris and Kleyheeg (2017) found major negative effects in 17% of 202 tracking studies of waterfowl, encompassing all attachment methods. Most recently, Bodey et al (2018) conducted a series of phylogenetically controlled meta-analyses of 214 studies incorporating control groups, finding small but significant negative effects of devices on survival, reproduction and parental care, and that foraging trips were longer in marked birds.…”
Section: Introductionmentioning
confidence: 99%